Local organizations and urban governance in East and Southeast Asia [ straddling state and society - Pekkanen, Robert; Read, Benjamin Lelan (Routledge studies on civil society in Asia, 2009)
Presents pieces of research on the many forms of organization in East and Southeast Asia that are sponsored or mandated by government, but engage widespread participation at the grassroots level. This book is suitable for undergraduates, postgraduates and academics in Asian studies, political science, sociology, anthropology, and development